What is the effect of Kegel exercises and the use of vaginal cones to strengthen the pelvic floor muscles? (Research, Society and Development, 2022)
Objective: The research sought to verify and discuss the methods for assessing pelvic floor strength existing in the literature in the last 20 years, as well as techniques for strengthening them. Methods: The research was based on a literature review of the literature in the MEDLINE, LILACS, SCOPUS, SciELO, BDENF and CUIDEN databases, between January and June 2018. Results: There are several ways to assess the function of the floor muscles pelvic and bidigital palpation and perineometry are the most effective. As for the forms of strengthening, kegel exercises associated with vaginal cones are important techniques, as they promote sensory feedback to the patient and are cost-effective. Being the professional nurse able to carry out nursing consultations in urogynecology, they can promote the prevention and cure of UI. Conclusion: The analysis of the studies allowed us to see in a holistic way that there are several ways to assess the function of the pelvic floor muscles, among which bidigital palpation and perineometry stand out, as they are the most effective.